565 Delayed Rupture Risk of Persistently Filling Saccular ICA Aneurysms Following Flow Diversion with the Pipeline Embolization Device. (April 2023) - Lee, Ryan P.; Bhimreddy, Meghana; Kim, Jennifer E.; Wicks, Robert Thomas; Xu, Risheng; Bender, Matthew T.; Jackson, Christopher Mitchell; Gonzalez, L. Fernando; Tamargo, Rafael Jesus; Caplan, Justin M.
Abstract : INTRODUCTION: Flow diversion of intracranial aneurysms results in high occlusion rates. However, 10-20% of aneurysms remain persistently filling on one year angiography. Often, these are retreated, but risks and benefits of retreatment are not well established. Calculating benefit requires a better understanding of rupture risk of persistently filling flow diverted aneurysms, which is not sufficiently established. METHODS: Our single institution database of 1000 flow diversion cases was queried for persistently filling saccular aneurysms of the clinoidal, ophthalmic, and communicating segments of the internal carotid artery treated with Pipeline Embolization Device or Pipeline Flex. Persistent filling was defined as continued contrast flow into the aneurysm on catheter angiogram one year after treatment. The clinical record was queried for occurrences of retreatment and delayed subarachnoid hemorrhage. Only cases with at least two years of follow up were included. RESULTS: Ninety-four persistent aneurysms were identified. The average size was 6 mm. The branch vessel originated separately from the aneurysm in 55% of cases, from the body of the aneurysm in 10.6% of cases, and from the neck in 34% of cases. Eighteen percent of aneurysms demonstrated >95% filling at one year and 61% were filling 5-95% of their original size. Average follow up time was 4.9 years, including 23 cases with >5 years follow up. No retreatment was undertaken in 91.5% of aneurysms. There were no cases of delayed subarachnoid hemorrhage. CONCLUSIONS: In our cohort of saccular ICA aneurysms treated with Pipeline flow diversion that demonstrated persistent aneurysm filling at one year, there were no instances of delayed rupture during the study period. This data suggests that observation may be appropriate for continued aneurysm filling at least in the first several years following Pipeline placement.